2018
DOI: 10.3390/ijms19072017
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Thyroid Hormone Signaling in Hypothalamic Control of Metabolism: Crosstalk Between Nuclear Receptors

Abstract: The obesity epidemic is well recognized as a significant global health issue. A better understanding of the energy homeostasis mechanisms could help to identify promising anti-obesity therapeutic strategies. It is well established that the hypothalamus plays a pivotal role governing energy balance. The hypothalamus consists of tightly interconnected and specialized neurons that permit the sensing and integration of several peripheral inputs, including metabolic and hormonal signals for an appropriate physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 174 publications
(208 reference statements)
1
15
0
2
Order By: Relevance
“…In mammals, the thyroid axis regulates food intake, body weight (309) and metabolic/nutrient homeostasis (310). The thyroid axis can influence feeding via the actions of TRH and THs in the brain, THs in the periphery, and also be influenced by endocrine appetite-regulating signals (e.g., NPY, leptin).…”
Section: Role Of the Thyroid Axis In Feeding/food Intakementioning
confidence: 99%
“…In mammals, the thyroid axis regulates food intake, body weight (309) and metabolic/nutrient homeostasis (310). The thyroid axis can influence feeding via the actions of TRH and THs in the brain, THs in the periphery, and also be influenced by endocrine appetite-regulating signals (e.g., NPY, leptin).…”
Section: Role Of the Thyroid Axis In Feeding/food Intakementioning
confidence: 99%
“…Upon ligand binding, THRs assemble into a co‐activator complex with histone acetyltransferase activity that is recruited to stimulate transcription (Lonard & O'Malley, 2007; Perissi et al, 2010). Moreover, THR interacts with other nuclear hormone receptors, such as peroxisome proliferator‐activated receptors, retinoid X receptors, retinoic acid receptors, and liver X receptors that allow binding to a wide repertoire of nucleotide sequences that contribute to regulate different metabolic pathways, including cholesterol, glucose, and fatty acid metabolism in different tissues (Brent, 2012; Kouidhi & Clerget‐Froidevaux, 2018). In addition, THs also modulate molecular pathways via protein–protein interactions such as PI3 K‐AKT‐FOXO1 and mTOR‐p70S6 K signaling, which further modulate transcription (Cao et al, 2005; Davis et al, 2016; Flamant et al, 2017; Mullur et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of DNAJC27 in HEK-MC4R cells reduced the efficacy of the MC4Rmediated formation of cAMP by two MC4R agonists, NDP-α-MSH and setmelanotide. Previous studies have reported that the activity of MC4R is a key modulator of food intake; stimulating MC4R induced satiety whereas blocking MC4R increased the appetite (1,3,8). Furthermore, loss-of-function genetic variants of MC4R are associated with obesity whereas gain-of-function genetic variants are protective against obesity (22).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, AgRP neurons project into the PVH releasing AgRP, which blocks MC4R. This results in the activation of appetite and an increase in food intake (1,3,8).…”
Section: Introductionmentioning
confidence: 99%